STUDI KERUSAKAN PERMUKAAN JALAN DENGAN METODE PCI PADA RUAS JALAN SEKARBELA KOTA MATARAM - Taufikurrahman, Taufikurrahman (Nusantara Hasana Journal, 2025)
Roads play a crucial role in human life. Adequate infrastructure support is essential, one of which is the availability of roads. Road damage can cause significant losses, directly impacting road users. Several road infrastructures in Mataram City are affected by flooding and runoff, such as in the Kekalik area (Jalan Swasembada). The impact on road construction is the deformation of the road surface layer, which leads to a decline in road performance. Therefore, an analysis of the level of pavement structural damage on the studied road sections is necessary using the PCI (Pavement Condition Index) method for several segments, both flooded and unflooded. The PCI method has a value ranging from 0 (severely damaged) to 100 (perfect). Calculating the PCI value involves calculating the density, deductible value (DV), total deductible value (TDV), corrected deductible value (CDV), and PCI value. Based on the research results, the types and average levels of damage on the Swasembada Kekalik Road section from km 0+000 to km 0+300 included: subsidence (6.22%), edge cracks (3.22%), vertical slopes (8.22%), patches (4.25%), potholes (1%), and grain detachment (27.33%). The Pavement Condition Index (PCI) values for each study segment indicate that the average pavement quality of the Swasembada Kekalik Road section is 36.33%, which is considered poor.